Identified Factors of the Effects of Excessive Usages of Smartphone on Health of the University Students: A Study on Islamic University, Kushtia, Bangladesh - Rahman, Taushif; Rahman, Md. Mizanoor; Sabur, Md. Abdus; Huda, Md. Nazmul (Archives of Business Research, 2022)
The objective of the study is to find out the effects of excessive use of smartphone on the health of the university students in Bangladesh. A closed ended questionnaire with five point Likert scale is used to collect data as the scores of agreed level for different selected issues. A total number of 289 respondents out of 350 students provide information willingly that covers 83% of total respondents. The data collection period was June, 2022. The non-parametric statistical techniques like Mann-Whitney U test and Kruskal Wallis test are mainly used to analyze the data. Excessive uses of smartphone are impacted badly on the sound health of the university students. These students having complications with different types of uncomfortable health conditions are not performing well not only in the academic activities but also in accomplishments of their everyday life. It is necessity to find out the ways of effective uses of smartphone for the university students to overcome the antagonistic situations.